ANALYSIS OF STUDENT RESPONSE TO TEACHER’S WRITTEN CORRECTIVE FEEDBACK IN WRITING DESCRIPTIVE TEXT - Emalia Kurnia Ananda; Mahmud Layan Hutasuhut (Universitas Negeri Medan, 2022)
The goals of this research are to describe students’ responses to teacher written corrective feedback in their descriptive texts and to discover types of written corrective feedback used by the teacher. Descriptive qualitative was used as the research methodology. The subjects of the study are a seventh year class of SMP Negeri 1 Tanjung Beringin consisting of 16 students and an English teacher. Open-ended interview and documentation review as the research instruments to collect the data. Result of the study revealed that (1) The students showed positive responses to teacher’s written corrective feedback. (a) They said that teacher written corrective feedback is a good thing to do. (b) They felt pleased when their descriptive texts being given teacher’s wtitten corrective feedback. (c) teacher’s written corrective feedback could make them motivated in writing. (d) They hoped the teacher always had provided their writing errors with written corrective feedback. (d) direct written corrective feedback being the most prefered teacher’s feedback by the students. and (2) From three types of written corrective feedback (metalinguistic, direct and indirect), teacher only used two of them, namely direct and indirect written corrective feedback in the students’ descriptive texts.